Physiologic and Anatomic Assessment of a Canine Carotid Artery Stenosis Model Utilizing Phase Contrast with Vastly Undersampled Isotropic Projection Imaging - Turk, A.S. (AJNR Am J Neuroradiol, 2007)
BACKGROUND AND PURPOSE: Noninvasive assessment of the hemodynamic significance of carotid stenosis is often performed with MR angiography and supplemented with carotid Doppler sonography. Phase contrast with vastly undersampled isotropic projection reconstruction (PC-VIPR), a novel MR imaging technique, accelerates phase-contrast MR flow imaging and provides both images of the vessels and measurements of blood-flow velocities. For this study, we determined the accuracy of PC-VIPR blood-flow velocity measurements to determine pressure gradients across an experimental carotid stenosis. MATERIALS AND METHODS: A focal stenosis was surgically created in each common carotid artery of 6 canines. Digital subtraction angiography (DSA) was performed, and the degree of stenosis was determined using the North American Symptomatic Carotid Endarterectomy Trial methodology. A microcatheter was positioned in the carotid artery proximal and distal to the stenosis, and pressures were measured in the vessel through the catheter. PC-VIPR was then performed on a 1.5T MR imaging scanner with parameters producing 0.8-mm isotropic voxel resolution. From the velocity measurements, pressure gradients were calculated from the Navier-Stokes relationship to compare with the pressures measured by a catheter. RESULTS: Carotid stenoses in the 50%–85% range were produced in the 12 arteries. Pressure gradients across the stenoses ranged from 6 to 26 mm Hg. The pressure gradient calculated from the PC-VIPR data correlated (r = 0.91, P < .0001) with the actual pressure measurements. CONCLUSION: With PC-VIPR, a novel MR imaging technique, the hemodynamic effect of a stenosis on flow and pressure can be evaluated.